2006
DOI: 10.1093/jxb/erj196
|View full text |Cite
|
Sign up to set email alerts
|

Controlled levels of salicylic acid are required for optimal photosynthesis and redox homeostasis

Abstract: Sudden exposure of plants to high light (HL) leads to metabolic and physiological disruption of the photosynthetic cells. Changes in ROS content, adjustment of photosynthetic processes and the antioxidant pools and, ultimately, gene induction are essential components for a successful acclimation to the new light conditions. The influence of salicylic acid (SA) on plant growth, short-term acclimation to HL, and on the redox homeostasis of Arabidopsis thaliana leaves was assessed here. The dwarf phenotype displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
253
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(285 citation statements)
references
References 85 publications
24
253
2
6
Order By: Relevance
“…These results are in agreement with earlier findings where SA treatment increased the reduced glutathione content and decreased that of the oxidized form, leading to an increased GSH/GSSG ratio in pea [35]. It was also reported that controlled levels of SA were required for optimal redox homeostasis [36]; furthermore, a relationship between SA and GR or GST was detected in the wheat x powdery mildew host x pathogen interaction [37]. The present results suggest that the increased SA level during Cd stress in the roots of Mv8 and Mv…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with earlier findings where SA treatment increased the reduced glutathione content and decreased that of the oxidized form, leading to an increased GSH/GSSG ratio in pea [35]. It was also reported that controlled levels of SA were required for optimal redox homeostasis [36]; furthermore, a relationship between SA and GR or GST was detected in the wheat x powdery mildew host x pathogen interaction [37]. The present results suggest that the increased SA level during Cd stress in the roots of Mv8 and Mv…”
Section: Discussionsupporting
confidence: 93%
“…82 LSD1 protects plants from ROS-induced stresses and consequently, lsd1 mutant plants are characterized by runaway cell death (rcd). 79,83 Therefore, lsd1 can be regarded as a sensitized mutant with respect to cell death initiation, and it has been instrumental in identifying other components of the signaling pathway leading to programmed cell death. For example, EDS1 and PAD4 functions are required for lsd1 rcd induced by abiotic stress.…”
Section: Regulators Of Plant Cell Deathmentioning
confidence: 99%
“…For example, EDS1 and PAD4 functions are required for lsd1 rcd induced by abiotic stress. 83 EDS1, PAD4 and NDR1 are also required for full lsd1 rcd in response to pathogen infection. 84 EDS1 and PAD4 regulate a ROS-and SA-dependent signal amplification loop, which in turn is modulated by LSD1.…”
Section: Regulators Of Plant Cell Deathmentioning
confidence: 99%
“…A very widely-found local defense mechanism is the generation of ROS as a hypersensitive response of plants to pathogens and subsequent stress on the colonizing microbes or neighboring roots (Blokhina et al 2003;Bolwell et al 1995;Hartmann et al 2009;Lamb and Dixon 1997;Mori and Schroeder 2004). Increased disease resistance is very likely to be a combinatorial effect of redox signals triggered by salicylic acid, H 2 O 2 , glutathione, and potentially additional yet unidentified compounds (Mateo et al 2006). The ascorbate-glutathione (AsA-GSH) cycle serves as the main antioxidant pathway in plant cells, linking protection against ROS to redoxregulated plant defenses (Kuzniak 2010).…”
Section: Redox Homeostasismentioning
confidence: 99%